Staff perspectives on end-of-life care for people living with dementia in residential aged care homes: qualitative study - Juhrmann, Madeleine L.; San Martin, Aljon; Jaure, Allison; Poulos, Christopher J.; Clayton, Josephine M. (Frontiers in Psychiatry, 2023)
Introduction: People living with dementia in care homes can benefit from palliative approaches to care; however, not all will require specialist palliative care. The generalist aged care workforce is well placed to provide most of this care with adequate training and support systems in place, but little is known about their experiences. Objective: To describe staff perspectives on providing quality end-of-life care for people living with dementia in residential care and their families. Methods: Focus groups and semi-structured interviews were conducted with residential aged care managerial and frontline staff in Australia who were caring for residents living with dementia and end-of life needs. A comprehensive, then snowballing sampling strategy was used in participating care homes. Transcripts were analysed using reflexive thematic analysis. Results: 15 semi-structured interviews and six focus groups were undertaken with 56 participants across 14 sites across two Australian states. Five themes were identified: putting the resident at the centre (creating homes not hospitals, knowing the individual, a case management approach); articulating goals to grant wishes (initiating the conversation, broadening death literacy, avoiding hospitalisation); a collective call to action (staffing the home, recognising deterioration and escalating issues, communication channels and engaging GPs, managing medications, psychosocial supports); educating to empower staff (governance and guidance, mentoring juniors, self-care); and facilitating family acceptance (setting expectations, partnering in care, access at all hours). Discussion: Aged care staff are committed to providing person-centred palliative and end-of-life care for people living with dementia, recognising the intrinsic value of each resident, regardless of their declining state. Frontline and managerial staff consider advance care planning, collectively working as part of a multidisciplinary team, access to targeted palliative and end-of-life education and training, and engaging families as key priorities to providing high quality care in care homes.